Expectativas e satisfação de adultos mais velhos com osteoartrite de joelho em relação à um projeto extensionista de Fisioterapia Aquática - de Matos, Paola Martins; Martins, Juliana Márcia; Gomes, Wellington Fabiano; Ferreira, Célio Marcos dos Reis; Bastone, Alessandra de Carvalho (Revista Vozes dos Vales: Publicações Acadêmicas, 2025)
Osteoarthritis is a chronic disease of high prevalence, and the knee is the most commonly affected joint. Pain affects mobility and daily activities. Aquatic physical therapy presents robust evidence of its effectiveness in managing this condition. This study aimed to describe the expectations and level of satisfaction of individuals with knee osteoarthritis in relation to an aquatic physiotherapy program. The study was conducted with 22 individuals (20 women and 2 men), participants in the extension project "Aquatic Physical Therapy for Older Adults with Knee/Hip Osteoarthritis." Individuals aged 45 years or older with a clinical diagnosis of knee osteoarthritis were included in the study. Participants completed a semi-structured questionnaire to share their expectations regarding the program. After three months of intervention, they completed another semi-structured questionnaire, which addressed their satisfaction with the program. Regarding expectations, the most frequently cited benefits were: pain relief (18 times), opportunity for socialization (8 times), improvement in well-being (5 times), and increased goodwill (5 times). After the intervention period, all participants reported feeling safe during pool activities and stated that the program contributed positively to their quality of life, fully meeting their initial expectations. The main benefits noted were: pain reduction (19 times), increased goodwill (10 times), and socialization (6 times). We concluded that the participants' expectations and level of satisfaction were broadly positive.
Keywords: Aquatic physical therapy; Expectations; Satisfaction; Osteoarthritis